2019
DOI: 10.3389/fphar.2019.00941
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoke Reduces Fatty Acid Catabolism, Leading to Apoptosis in Lung Endothelial Cells: Implication for Pathogenesis of COPD

Abstract: Endothelial cell (EC) apoptosis contributes to cigarette smoke (CS)-induced pulmonary emphysema. Metabolism of glucose, glutamine, and fatty acid is dysregulated in patients with chronic obstructive pulmonary disease (COPD). Whether CS causes metabolic dysregulation in ECs leading to development of COPD remains elusive. We hypothesized that CS alters metabolism, resulting in apoptosis in lung ECs. To test this hypothesis, we treated primary mouse pulmonary microvascular ECs (PMVECs) with CS extract (CSE) and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 39 publications
(53 reference statements)
1
42
0
Order By: Relevance
“…However, the levels of macrophage, T cell, neutrophil, and eosinophil in the lungs of patients with pulmonary emphysema were increased multiple-folds compared with the normal group. This finding suggests that the inflammatory response toward smoke is elevated in patients with pulmonary emphysema [17]. In the studies using mouse models exposed to chronic cigarette smoke, amplified inflammatory cells including phagocyte, neutrophil, and T cell were observed in lung, and these cells and mediators were found to participate in the COPD chronic inflammation and affect the balance between oxidation and antioxidation [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…However, the levels of macrophage, T cell, neutrophil, and eosinophil in the lungs of patients with pulmonary emphysema were increased multiple-folds compared with the normal group. This finding suggests that the inflammatory response toward smoke is elevated in patients with pulmonary emphysema [17]. In the studies using mouse models exposed to chronic cigarette smoke, amplified inflammatory cells including phagocyte, neutrophil, and T cell were observed in lung, and these cells and mediators were found to participate in the COPD chronic inflammation and affect the balance between oxidation and antioxidation [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we have investigated the protective ability of prohibitin overexpression in CSE exposure associated mitochondrial dysfunction, ROS generation, oxidative DNA damage and apoptosis in HPMECs. CSE may induce apoptosis in bronchial epithelial cells, endothelial cells and human airway smooth muscle cells (ASMCs) [11][12][13][14] CSE may cause injury in mitochondrial morphology and function and induce apoptosis via an intrinsic apoptotic pathway, which involves mitochondrial fragmentation and the disruption of mitochondrial membrane integrity, inhibit of mitochondrial respiration and release of cytochrome c, as well as changed expression levels of pro-apoptotic and anti-apoptotic molecules [13,[15][16][17][18]. A previous study has demonstrated that prohibitin decrease the apoptosis of endothelial cells in response to glyLDL [19].…”
Section: Discussionmentioning
confidence: 99%
“…CSE may induce apoptosis in bronchial epithelial cells, endothelial cells and human airway smooth muscle cells (ASMCs) [11][12][13][14] CSE may cause injury in mitochondrial morphology and function and induce apoptosis via an intrinsic apoptotic pathway, which involves mitochondrial fragmentation and the disruption of mitochondrial membrane integrity, inhibit of mitochondrial respiration and release of cytochrome c, as well as changed expression levels of pro-apoptotic and anti-apoptotic molecules [13,[15][16][17][18]. A previous study has demonstrated that prohibitin decrease the apoptosis of endothelial cells in response to glyLDL [19].…”
Section: Discussionmentioning
confidence: 99%